Octopus++: an enhanced mutual authentication security protocol and lightweight encryption and decryption algorithm based on DNA in fog computing - Rahman, Gohar (2023)
The Internet of Things (IoT) envisions a world wherein everyday objects may connect to the internet and exchange data, analyse, store, and gather data from their environment and efficiently mediate on it. Fog computing, closer to the IoT, is formulated in data processing, filtering, aggregating, and storing. In fog IoT network one of the main challenges is security. The existing security solutions are based on modern cryptography algorithms are computationally complex which causes the fog IoT network to slow down. Therefore, in fog IoT the operations must be lightweight and secure. The security considerations include attacks, especially Man in the Middle attack (MitM), challenges, requirements, and existing solutions that are deeply analyzed and reviewed. Hence, omega network key generation based on deoxyribonucleic acid (ONDNA) is proposed, which provides lightweight encryption and decryption in fog computing. The security level of ONDNA is tested using NIST test suite. ONDNA passes all the 17 recommended NIST Test Suite tests. Next, we proposed a modified security protocol based on ONDNA and hash message authentication code with secure hash algorithm 2. The modified protocol is noted as OCTOPUS++. We proved that the OCTOPUS++ provides confidentiality, mutual authentication, and resistance to MitM attack using the widely accepted Burrows Abdi Needham (BAN) logic. The OCTOPUS++ is evaluated in terms of execution time. The average execution time for 20-time execution of OCTOPUS++ is 1.018917 milliseconds. The average execution time for Octopus, LAMAS and Amor is 2.444324, 20.1638 and 14.1152 milliseconds respectively. The results show that the OCTOPUS++ has less execution time than other existing protocols